2011
DOI: 10.1509/jm.10.0088
|View full text |Cite
|
Sign up to set email alerts
|

Seeding Strategies for Viral Marketing: An Empirical Comparison

Abstract: Seeding strategies have strong influences on the success of viral marketing campaigns, but previous studies using computer simulations and analytical models have produced conflicting recommendations about the optimal seeding strategy. This study compares four seeding strategies in two complementary small-scale field experiments, as well as in one real-life viral marketing campaign involving more than 200,000 customers of a mobile phone service provider. The empirical results show that the best seeding strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
418
5
20

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 533 publications
(463 citation statements)
references
References 46 publications
(60 reference statements)
20
418
5
20
Order By: Relevance
“…Given companies' intention to expand customer relationships and to increase customer revenues, WOM affects not only the sales of other customers (Chevalier and Mayzlin 2006;Hinz et al 2011) but also the sales of the senders, repeat purchases, or additional purchases through up-or cross-selling (Kumar et al 2010;Armelini et al 2015). Up-or cross-selling in the mobile phone context could involve extended talk or data plans, hardware, or auxiliary services (e.g., Company: ''Upgrade your data plan and get 1 GB data free!'').…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Given companies' intention to expand customer relationships and to increase customer revenues, WOM affects not only the sales of other customers (Chevalier and Mayzlin 2006;Hinz et al 2011) but also the sales of the senders, repeat purchases, or additional purchases through up-or cross-selling (Kumar et al 2010;Armelini et al 2015). Up-or cross-selling in the mobile phone context could involve extended talk or data plans, hardware, or auxiliary services (e.g., Company: ''Upgrade your data plan and get 1 GB data free!'').…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…DOI: http://dx.doi.org/10.1108/JRME-07-2015-0039 (Bjerke & Hultman, 2002). Some entrepreneurial marketing tactics include word of mouth marketing (Keller, 2007), viral marketing (Hinz, Skiera, Barrot, & Becker, 2011) and buzz marketing (Hausmann, 2012;Thomas, 2004). While analysing the marketing practices of successful entrepreneurs, Stokes (2000) found that they tend to serve a small base of customers and expand based on resource availability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Before abandoning emails to customers and jumping on the next bandwagon of electronic communication method, e-tailers should consider using each form of communication as a way of targeting consumers. In particular, seeding strategies may focus on well-connected consumers within the social networks (Hinz et al 2011). Organizations should implement programs to better understand different forms of social networking to enhance their seeding strategies in order to maximize E-WOM.…”
Section: Managerial Contributionsmentioning
confidence: 99%